APPLIED ECOLOGY FOR IRRIGATION ENGINEERS - R. E. Regel; A. A. Fedotova; N. P. Goncharov (Вавиловский журнал генетики и селекции, 2014)
The year 2012 marks several important anniversaries in the history of applied botany in Russia. The activity of the individuals celebrated in this year has resulted in the establishment of a research institute and gene bank: the Vavilov Institute of Plant Industry (VIR, St. Petersburg), which keeps one of the most significant collections of cultivated plant seeds in the world. We also celebrate the 125th anniversary of N.I. Vavilov, VIR’s most well-known director. In addition, this year celebrates Alexandr F. Batalin, Ivan P. Borodin, and Robert E. Regel, who were the first, third, and fourth managers of VIR’s predecessor organization, the Bureau for Applied Botany.To honor these anniversaries we publish here Regel’s memorandum on the teaching of botany and applied ecology for irrigation engineers, a document recently discovered in the Russian State Historical Archive (St. Petersburg). As an introductory article, we offer a brief essay on Regel’s scientific and organizational activities, which describes his role in the establishment of applied botany as a scientific discipline in Russia.It is supplemented by new archival documents.